The Effect of Burnout and Employee Engagement on Turnover Intention with Work-Life Balance as a Mediating Variable in Millennial Employees of PT. ABC and PT. XYZ in Bekasi Regency - Ambarwati, Ayu; Setyaningrum, Retno Purwani; Rezeki, Fitri (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
After Covid-19 that occurred in early 2020, the world of work has undergone dramatic changes over the past few decades. The technological revolution, especially the development of the internet and digital communication has made it possible for many employees to work from anywhere. Work that can be accessed anytime and anywhere results in many people having difficulty separating work from their personal lives. This can lead to an imbalance between work and life, where work becomes more dominating of an individual's time and attention. The purpose of this study is to create and develop an empirical conceptual model of how burnout and employee engagement can affect turnover intention with work-life balance being a mediating variable. The research method is a quantitative method with the distribution of questionnaires which are then processed using SmartPLS 3.0. The result of the study was Burnout has a positive and significant effect on turnover intention. Employee involvement has a positive but not significant influence on turnover intentions. Burnout has a negative but not significant effect on work-life balance. Employee engagement has a positive and significant effect on work-life balance. Work-life balance has a negative but not significant effect on turnover intentions. Work-life balance cannot mediate burnout and employee engagement against turnover intentions.